First Episode Psychosis and Pituitary Hyperplasia in a Patient With Untreated Hashimoto’s Thyroiditis: A Case Report - Lipkes, Celeste; Haider, Shanzay; Rashid, Ali; Angarita, Gustavo A.; Riley, Sarah (Frontiers in Psychiatry, 2022)
This case report describes a woman with no psychiatric history and previously diagnosed Hashimoto’s thyroiditis who presented to the psychiatric emergency department with a first episode of psychosis. The initial workup for organic causes of psychosis revealed an astronomically high TSH (>1,000 μIU/mL) out of proportion to the patient’s minimal physical symptoms of hypothyroidism. Additionally the patient’s head imaging showed an enlarged pituitary, a rare, but reversible, presentation of chronically untreated primary hypothyroidism. The patient was transferred to a medical unit to receive IV thyroid replacement as well as an adjunctive antipsychotic to assist with remission of her distressing auditory hallucinations and persecutory delusions. This case highlights the importance of a thorough medical workup for causes of new onset psychosis and the need for further consensus in the literature regarding choice of antipsychotic and duration of treatment for psychosis secondary to hypothyroidism.